Signed food: who is the author of the #foodart? - Piluso, Francesco (E|C, 2020)
Baudrillard (1972) highlighted how the author's signature restores the aura lost in the era of its reproducibility to the work of art. Today, the mechanism of authorship is necessary to give an aura of prestige to the world of cooking. However, if in the case of works of art the simulation resided in the insane speculation on the value of the signed series (and the prestige of participating in this game on the upside), in the case of the kitchen it is the serialized signature itself that is simulated and placed as a sanction for something already in series and pre-valued.